El señalakuy - Delgado Aragón, Julio (1971)
The popular masses in the District of Macusani, of the Province of Carabaya, of the Department of Puno, are almost entirely made up of the peasant element, which is improperly called "Indian", which constitutes the deepest stratum of our tradition. His way of being, his manifestations, his tendencies and the reactions he experiences before the influence of the environment in which he carries out his activities, are rich seams of knowledge, which have remained on many occasions, covered with the black cloak of oblivion, despite the fact that they make up the survival of the past, which has remained in the recesses of the collective soul, as a living archive of a generation that, after having fully lived in its historical moment, has left; revealing the gesture of a race with a great ideal forged on the anvil of time and a deep sentimentality. Those legends, myths, customs that wander in the mouths of the centenarian Indians and that they keep as a symbol of the greatness of their ancestors and that with certain adulterations still practice them, serve to interpret so many enigmas, which sustain the very roots of our nationality.